Fiscal Reconciliation Analysis of Commercial Reports in the Determination of Corporate Income Tax (Case Study on Grand Jamee Sharia Hotel) - Aini, Nurul (Accounting and Business Journal, 2025)
This research aims to analyze the fiscal reconciliation process conducted by Hotel Syariah Grand Jamee to determine corporate income tax. The core issue addressed is the discrepancy between commercial and fiscal financial statements arising from the application of PSAK and tax regulations in Indonesia. A descriptive-quantitative approach was used to analyze financial data from the year 2023. The findings indicate a total positive fiscal adjustment of IDR 114,127,906, comprising non-deductible donations (IDR 33,983,623), excess consumption expenses (IDR 71,364,078), and unsupported miscellaneous expenses (IDR 8,780,205). These adjustments reduced the fiscal loss from IDR 611,247,618 to IDR 497,119,712. Despite these corrections, the company reported zero corporate income tax payable due to the remaining fiscal loss. The results emphasize the critical importance of accurate and systematic fiscal reconciliation to minimize the risk of administrative sanctions and potential tax disputes. This study provides practical insights for businesses in aligning their commercial financial reports with prevailing tax regulations, thereby ensuring compliance and reducing legal and financial risks.